2016
DOI: 10.18632/oncotarget.10504
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of thiacremonone on MPTP-induced dopaminergic neurodegeneration through inhibition of p38 activation

Abstract: Neuroinflammation is implicated for dopaminergic neurodegeneration. Sulfur compounds extracted from garlic have been shown to have anti-inflammatory properties. Previously, we have investigated that thiacremonone, a sulfur compound isolated from garlic has anti-inflammatory effects on several inflammatory disease models. To investigate the protective effect of thiacremonone against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced behavioral impairment and dopaminergic neurodegeneration, 8 week old I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…This neuroprotective activity of Allium sativum is attributed to the ability of garlic-derived organosulfur compounds-DAD and DAT-to modulate redox activity and to reduce oxidative stress and their incorporation in many signaling pathways [47]. Diallyl disulfide was proven as a strong lipid peroxidation terminator [55], thus providing neuronal protection and preventing neuronal damage by excitotoxins. The protective effect of Allium sativum against MSG-induced hippocambal neurons agreed with the finding of Hwang et al [55], who reported that garlic protected dopaminergic neurons from degeneration in a Parkinson rat model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This neuroprotective activity of Allium sativum is attributed to the ability of garlic-derived organosulfur compounds-DAD and DAT-to modulate redox activity and to reduce oxidative stress and their incorporation in many signaling pathways [47]. Diallyl disulfide was proven as a strong lipid peroxidation terminator [55], thus providing neuronal protection and preventing neuronal damage by excitotoxins. The protective effect of Allium sativum against MSG-induced hippocambal neurons agreed with the finding of Hwang et al [55], who reported that garlic protected dopaminergic neurons from degeneration in a Parkinson rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Diallyl disulfide was proven as a strong lipid peroxidation terminator [55], thus providing neuronal protection and preventing neuronal damage by excitotoxins. The protective effect of Allium sativum against MSG-induced hippocambal neurons agreed with the finding of Hwang et al [55], who reported that garlic protected dopaminergic neurons from degeneration in a Parkinson rat model. The authors also found that it decreased astrocyte activation and neural inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…MPTP is a commonly used chemical to induce a PD-like state in rodents [ 13 14 ]. As animals do not develop PD, the MPTP lesion model is one of several models that are used to investigate the underlying mechanisms of PD and to test novel compounds for their neuroprotective properties [ 15 ]. This study investigated the neurogenesis and PD recovery effects of CB2R agonist, AM1241, treatment in MPTP-induced PD mice.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitor of JNK, SR-3306, can reduce the loss of neurons in a rat model of PD, suggesting that JNK inhibitors possess a protective effect on neurons in PD (35). p38 is also activated in neurotoxic PD models (36). Furthermore, inhibitors of p38 are effective in the treatment of PD (4).…”
Section: Discussionmentioning
confidence: 99%